Políticas sociais no Brasil: um enfoque sobre o orçamento geral da união de 1995 a 2010 - Silva, Cláudia Maria (2012)
This study aims to analyze the development of federal social spending (FSS) within the general budget of the Union. It is intended to understand what were the priorities of the federal budget expenditures with social policies from 1995 to 2010 in the governments Fernando Henrique Cardoso (FHC) - 1995 to 2002 and Luiz Inácio Lula da Silva (Lula) - 2003 to 2010, under the management of orthodox economic policy in a period of 16 years. Accordingly, the issue to be investigated is: governments with speeches and seemingly different characteristics may in practice have led expenditure on social policies in a similar way? To answer this question we consider the influences of neoliberal thinking in macroeconomic policy from the 1990s, which contributed significantly to increase spending to service their debt, favoring the financial sector of the economy to the detriment of social. In the data analysis we also dispense attention to expenditures directed to pay interest, taxes and amortization of public debt (internal and external), because the presence of a high cost of debt can be singled out as a major limiting public spending by the federal government, especially for social policies. The evolution of budget execution revealed the vulnerability of social spending during periods of crisis, and a significant expansion of budget spending in periods of relative recovery of economic growth with lower financial costs (interest and debt charges) and less fiscal restraint. However, the increase in FSS allowed an expansion of social protection that should not be underestimated. The trajectory of FSS proved irregular and unstable only in periods of economic or political crisis, one of the concerns of this study was to relate this instability to macroeconomic policy. It is observed that the changes in economic policy management - clearly demarcating the four presidential terms from this period - strongly conditioned the trajectory of FSS. Thus, to contextualize these expenses on the trajectory of federal spending and financial performance of the tax burden. Finally, it is important to note that the main contribution of this research is the analysis of social spending between the FHC and Lula, above all, in the analysis of social spending of the Lula government is not yet broad approach in the recent literature. In this sense, we hope that this mosaic be intelligible and that contributes to the debate between the various areas within the social sciences to help the country improve the living conditions of all of Brazilian society, especially among individuals who are in precarious situation, giving those to human dignity